Réponses

Meilleure réponse !
  • Utilisateur Brainly
2013-05-29T15:32:01+02:00

on considere l expression f=(5x+4)²-49                                                                                       

1) developper puis reduire F            

 f=(5x+4)²-49  

  =(5x+4-7)(5x+4+7)

  =(5x-3)(5x+11)

  =25x²-15x+55x-33

  =25x²+40x-33

                                                                  

2)factoriser F              

 f=(5x+4)²-49  

  =(5x+4-7)(5x+4+7)

  =(5x-3)(5x+11)

                                                                                                           

3) resoudre l equation (5x-3)(5x+ 11)=0       

  5x-3=0 ou 5x+11=0

donc x=3/5 ou x=-11/5

donc x=0,6 ou x=-2,2

                                         

4)calculer F pour x=-2

si x=-2 alors F=-13*1=-13